Improving the productivity of millet based cropping systems in the West African Sahel: Experiences from a long-term experiment in Niger - Bado, V.B.; Bationo, A.; Whitbread, Anthony M.; Tabo, Ramadjita; Laminou, M.; Manzo, S. (Elsevier, 2022)
Resource-poor farmers who are living in the harsh environments of the West African Sahel (WAS) depend on subsistence orientated, low-input farming systems for meeting their livelihood needs. These largely extractive farming systems have resulted in nutrient depletion, soil fertility decline, low productivity and land degradation. A study conducted over 25 years in Niger, aimed to evaluate the long-term effects of organic and mineral fertilizers, cropping systems (CS) of millet and cowpea on crop productivity. The traditional millet/cowpea intercrop system without P fertilizer (TrM/C) was compared with four improved CS receiving P fertilizer: sole millet (MM), millet/cowpea intercrop (M/C), millet-cowpea rotation (M-C), and M/C and rotation with cowpea (M/C-C). Nitrogen fertilizer (N) and the residues of millet (CR) were applied alone or in combination in all five cropping systems. CR were always applied as mulch. The traditional system (TrM/C) produced the lowest millet grain yields (GY) (0.02–0.43 t/ha). All the four improved CS (MM, M/C, M-C and M/C-C) increased GY compared with the traditional system (TrM/C). The M/C and MM systems increased millet GY 3 and 3.3 times compared with the TrM/C, respectively. The M/C-C and M-C systems produced 4 and 4.2 times more GY than that of the TrM/C system, respectively. The lowest revenue was obtained with the TrM/C system. Except for the TrM/C, the revenue of the MM system was lower compared with combined cultivation of millet and cowpea. Compared with the TrM/C system, M/C and M/C-C provided 2 times more revenue. By providing 2.4 times more revenue than the TrM/C system, the M-C system was the most productive system. Cowpea provided from 54% and 56% of the revenue in M/C-C and M-C system, respectively. Soil organic carbon decreased in all the CS from 46% to 63% compared with the soil kept under natural vegetation fallow. The improved CS increased soil P from 3.4 to 4 times. Over the 25 years of cropping, the highest millet yields were obtained with the lower levels of rainfall indicating the role of nutrients in the system. The four improved systems maintained millet yields over the 25 years of cropping. By improving water and nutrient use efficiency, integrated management of mineral fertilizers, CR and cowpea affected more crop productivity than rainfall. We concluded that cereal-legume-based cropping systems treated with small doses of mineral fertilizers and CR could be used for sustainable management of soil fertility in low-input farming systems.